Binding of tetrabutylammonium bromide based deep eutectic solvent to DNA by spectroscopic analysis - Yusof, Rizana; Jumbri, Khairulazhar; Ahmad, Haslina; Abdulmalek, Emilia; Abdul Rahman, Mohd Basyaruddin (Elsevier, 2021)
The binding characteristics of DNA in deep eutectic solvents (DESs), particularly the binding energy and interaction mechanism, are not widely known. In this study, the binding of tetrabutylammonium bromide (TBABr) based DES of different hydrogen bond donors (HBD), including ethylene glycol (EG), glycerol (Gly), 1,3-propanediol (1,3-PD) and 1,5-pentanediol (1,5-PD), to calf thymus DNA was investigated using fluorescence spectroscopy. It was found that the shorter the alkyl chain length (2 carbons) and higher EG ratios of TBABr:EG (1:5) increased the binding constant (Kb) between DES and DNA up to 5.75 × 105 kJ mol−1 and decreased the binding of Gibbs energy (ΔGo) to 32.86 kJ mol−1. Through displacement studies, all synthesised DESs have been shown to displace DAPI (4′,6-diamidino-2-phenylindole) and were able to bind on the minor groove of Adenine-Thymine (AT)-rich DNA. A higher number of hydroxyl (OH) groups caused the TBABr:Gly to form more hydrogen bonds with DNA bases and had the highest ability to quench DAPI from DNA, with Stern-Volmer constants (Ksv) of 115.16 M−1. This study demonstrated that the synthesised DESs were strongly bound to DNA through a combination of electrostatic, hydrophobic, and groove binding. Hence, DES has the potential to solvate and stabilise nucleic acid structures.